HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN TINDAKAN PENCEGAHAN PENYAKIT MENULAR SEKSUAL PADA ANAK BUAH KAPAL DI PELABUHAN BELAWAN 2019 - Isroni Azhari Siregar; Masryna Siagian; Herbert Wau (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2019)
The act of the prevention sexually transmitted infections disease is one of to reduce the spread of sexually transmitted to live a sex safety and health life style. According to A recent survey of beginning was conducted at Port Health Office of Medan in 2018, that knowledge and attitude of the crews still less about the use of contraseptives and the act of not doing a check health routinely. This study is an analitic research disign it is the cross section aimed analize ascertaining the knowledgeand attitudes of the prevention sexually transmitted infections disease. The population for this study were 254 crew. Samples were taken 72 crew. Data analysis is done by using chi-square with 95 % confidece level. The result of study revealed that there was a correlation of knowledge with the act of prevention sexually transmitted infection at Belawan port in 2019 (p=0,002<0,05), and there was a correlation of attitude with the act of prevention sexually transmitted infection at Belawan port in 2019 (p=0,000 <0,05) It was suggested that it is expected that Health Officer in Port Health Belawan will increase the socialization sexual transmitted infection disease, distribute brochurs or leaflet to crew member. It was also suggest to crew member that to increase knowledge and attitude regarding prevent of sexually transmitted infections, namely by attending counseling from port health officer, reading books and magazines related to sexually transmitted infections and through other media access so that prevention efforts are more optimal, so as to avoid themselves from contracting sexually transmitted infections. .